APPLICATIONS FOR STUDENT LEARNING PHYSICS INTEAKTIF SMP USING MACROMEDIA FLASH MX - Yogi Iriyanto; Cut Asiana Germawaty, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Progress of computer technology is so rapidly, supported by the advancement in information technology today, can actually be used to improve teaching and learning processes by using lesson packages that fit. In this case, the computer device used t o create learning programs that enable shared training activities undertaken, such as the presentation of information in the form of text, graphics, simulations, animations, exercises, and umpal directly behind.  One of compatible software and reliable standard is Macromedia Flash MX. Produced more vivid animation and interactivity to attract users, besides its use is relatively easier. In the process of learning the most important thing is learning itself can diaplikannya on specific disciplines that would be more meaningful and significant, especially in the field of physics. Therefore, creating an interactive learning physics in the form of a CD and can be taken anywhere SMP would be very helpful in understanding the learning itself because it is relative ly easier to use and relatively inexpensive.